Electrochemical behavior of ruthenium-hexacyanoferrate modified glassy carbon electrode and catalytic activity towards ethanol electrooxidation - Costa, Wendell M.; Cardoso, William S.; Marques, Edmar P.; Bezerra, Cicero W.B.; Ferreira, Antonio Ap.P. [UNESP]; Song, Chaojie; Zhang, Jiujun; Marques, Aldaléa L.B. (Sociedade Brasileira de Quimica (SBQ), 2013)
Ruthenium-based hexacyanoferrate (RuHCF) thin film modified glassy carbon electrode was prepared by drop evaporation method. The RuHCF modified electrode exhibited four redox couples in strong acidic solution (pH 1.5) attributed to Fe(CN)6 3- ion and three ruthenium forms (Ru(II), Ru(III) and Ru(IV)), characteristic of ruthenium oxide compounds. The modified electrode displayed excellent electrocatalytic activity towards ethanol oxidation in the potential region where electrochemical processes Ru(III)-O-Ru(IV) and Ru(IV)-O-Ru(VI) occur. Impedance spectroscopy data indicated that the charge transfer resistance decreased with the increase of the applied potential and ethanol concentration, indicating the use of the RuHCF modified electrode as an ethanol sensor. Under optimized conditions, the sensor responded linearly and rapidly to ethanol concentration between 0.03 and 0.4 mol L-1 with a limit of detection of 0.76 mmol L-1, suggesting an adequate sensitivity in ethanol analyses. Printed in Brazil - ©2013 Sociedade Brasileira de Química.
Keywords: Chronoamperometry; Cyclic voltammetry; Electrochemical impedance; Ethanol sensor; Ruthenium-hexacyanoferrate